Utilization of Palm Solid Residue For Bioethanol Production In Sumatra Indonesia – A Review - Enjelita, Anggun; Auralita, Kakalia Putri; Aprianti, Resah; Indrajaya, Zahra Afifa; Maulana, Ivan (Journal of Clean Technology, 2024)
The combustion of fossil fuels causes an increase in the release a group of gases found in the earth atmosphere that trap heat and contribute to the greenhouse effect, which in turn contributes to the occurrence of global warming. The advancement of sustainable energy sources plays an important role in human life due to renewable and environmentally friendly. This problem can be resolved by using alternative fuels as renewable sources of energy that are more environmentally friendly, such as bioethanol. Empty fruit bunches (EFB) constitute a portion of the solid waste that cause problems in storage, transportation, and processing costs. This is because EFB is waste in a solid that is produced from a processing facility where the fruits of the oil palm tree are processed to extract palm oil in large quantities. The process of producing bioethanol by utilizing coconut fruit bunches that are devoid of their contents as a raw material involves two essential stages: hydrolysis and drying. Hydrolysis with an acid catalyst results in a lower yield, but the catalyst itself is inexpensive. Conversely, when using enzyme catalysts, hydrolysis produces a greater quantity of reducing sugars. Enzyme catalysts can be employed in the simultaneous saccharification and fermentation (SSF) process using S. cerevisiae yeast, while chemical catalysts can be used in separate hydrolysis and fermentation (SHF) methods. The SSF method provides a comparatively elevated ethanol yield, demands less enzyme usage, has a shorter duration for ethanol production, and is environmentally friendlier when compared to the SHF procedure.